Territórios e afetos: decolonialidade em vasto mar de sargaços, de Jean Rhys - Barbosa, Ana Paula Herculano (2024)
Decolonial studies have emerged as a movement to re-elaborate perspectives in the production of knowledge, making it possible to reposition and review colonizing processes in the Americas. From this decolonial perspective, we analyzed our research corpus, the novel Wide Sargasso Sea ([1966]2016) by Caribbean writer Jean Rhys. Through the Rhysian narrative we get to know Antoinette, the novel's protagonist, who is followed from childhood to adulthood in her transits through different territories; she, a Creole woman from the local elite, grows up in colonial Jamaica after the Emancipation Act of 1833 (Freitas, 2017; Silva, 2021), under the strong influence of the modern-colonial system. By marrying an aristocratic English man, Antoinette began to suffer more directly from the violent practices disseminated by the colonial regime. In order to analyze the Rhysian novel on the basis of the decolonial turn (Segato, 2021;2022), we dealt with the concepts of territory, body, affection and violence on the basis of this perspective. In this way, we discuss the violence perpetrated against the protagonist and two other women- her mother Annette and her former nanny Christophine- by reading their bodies as territories. We also consider the reactions of these bodies-territories to the violence they suffer, with these violent acts being supported by the policies of the modern-colonial system. Still dealing with the concept of territory, now linked to affections, thinking of these as potency, we analyze the power of territoriality to affect the subject, directing our gaze to the way in which territories influence Antoinette. In order to achieve these objectives, we will begin by analyzing Rhysian work and the Brazilian academic production on Rhys's narratives. In order to enter the discussion on decoloniality, we turned to authors such as: Quijano (1992), Maldonado-Torres (2018), Mignolo and Walsh (2018), Segato (2012;2021;2022), Mendoza (2010), Ballestrin (2013), Dussel (2000) and Lugones (2014;2020). We deal with terminologies that involve the decolonial turn and that have enabled the development of the following sections, in which we discuss the violent acts that Antoinette, Annette and Christophine were victims and their reactions to this violence. When dealing with the relationship between territories and affections, we discussed the term affection and the bias we chose to follow when using it in our research, working with authors such as Ahmed (2014), Almeida (2015a;2015b), Deleuze (2019), Haesbaert (2020;2021), hooks (2021), Lara (2020;2021), Solana and Vaccarezza (2020a;2020b), among others. When dealing with territories of affections, we emphasize the influence of territoriality on subjectivities. Our analysis has allowed us to establish connections between decoloniality and the re-reading of the figure of the passive victim, a place that is not occupied by the characters Antoinette, Annette and Christophine; as well as being able to ascertain the importance of territoriality and affections for the protagonist Antoinette's practices of resistance.